Kajian dan Rekomendasi Sistem Pemetaan Lahan Pertanian - Halim Budi Santoso; Antonius Rachmat C; Rosa Delima; Argo Wibowo (ULTIMA InfoSys, 2020)
Implementation of Information Technology in agriculture sector is able to raise farming productivity. One of the Information Technology implementation is mapping system for agriculture land which has not only data collection but also strategic role. This paper discusses literature review of implementation of web mapping system, either from user perspective and functional perspective. On the end of the paper will discuss feature, opportunities, and challenges to develop and implement Web Mapping System. This paper also gives some recommendatios in order to support web mapping system implementation.